Low Circulating TRAIL Levels Are Associated with Increase of Resistin and Lipocalin-2/ngal Adipokines in Postmenopausal Women. (5th September 2017) - Tisato, Veronica; Secchiero, Paola; Bonaccorsi, Gloria; Bergamini, Carlo; Greco, Pantaleo; Zauli, Giorgio; Cervellati, Carlo
Abstract : Objective . Tumor necrosis factor- (TNF-) related apoptosis-inducing ligand (TRAIL) is attracting attention for its role in the physiopathology of metabolic disease/diabetes. Evidence suggests that it might protect against metabolic abnormalities driven by obesity-induced dysregulated secretion of adipokines, but this role of TRAIL has not yet been fully established. On this basis, we aimed to investigate the potential association between TRAIL and adipokine levels in a cohort of subjects in which age/gender/hormonal interferences were excluded. Methods . Serum levels of TRAIL and a panel of adipokines were measured in postmenopausal women (n = 147 ) stratified according to waist circumference measures as normal, overweight, or obese. The panel of adipokines included interleukin- (IL-) 6, IL-8, IL-1 β, adipsin, lipocalin-2/neutrophil gelatinase-associated lipocalin (ngal), TNF-alpha, monocyte chemoattractant protein-1, plasminogen activator inhibitor-1, hepatocyte growth factor, resistin, leptin, adiponectin, and nerve growth factor. Results . Low serum TRAIL concentration (deciles I–IV) was significantly and inversely correlated with resistin and lipocalin 2/ngal levels (r = − 0.502 and p < 0.001 and r = − 0.360 and p < 0.01, resp.). Both associations retained their statistical significance after adjustment for confounding factors, such as waist circumference and age. Conclusions . Our data indicate a link between low circulating levels of TRAIL and markers of obesity-induced diseases (resistin and lipocalin-2/ngal), highlighting a new potential axis of TRAIL functions.